2022
DOI: 10.1136/bmjopen-2021-056639
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health service utilization of young girls in rural Ethiopia: What are the roles of health extension workers? Community-based cross-sectional study

Abstract: ObjectiveLittle is known about the extent to which Health Extension Programme (HEP) has played its role to increase service uptake among young girls. This study aims to estimate the status of young girls’ sexual and reproductive health (SRH) services utilisation in rural Ethiopia and to examine the role of health extension workers (HEWs) in this regard.DesignA cross-sectional study.SettingA community-based study among all nine regions of Ethiopia.ParticipantsNine hundred and two young girls aged 15–24 years we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
0
1
Order By: Relevance
“…The ndings revealed that overall sexual and reproductive health service utilization was 27.4% (95%CI: 26.9, 27.8). This nding was higher than studies conducted in Gamo Gofa (16.9%) 15 Philippines (13.8%) 16 , Indonesia (24.3%) 17 East Gojam, Ethiopia (21.5%) 18 and Ethiopia 19.18%) 19 . However, lower than the study conducted in Jima Ethiopia, 41.1% 20 ; Eastern Ethiopia, 39.3% 21 ; Wolaita, Southern Ethiopia (49.8%) 22 and Kenya 36%) 23 .…”
Section: Discussioncontrasting
confidence: 57%
“…The ndings revealed that overall sexual and reproductive health service utilization was 27.4% (95%CI: 26.9, 27.8). This nding was higher than studies conducted in Gamo Gofa (16.9%) 15 Philippines (13.8%) 16 , Indonesia (24.3%) 17 East Gojam, Ethiopia (21.5%) 18 and Ethiopia 19.18%) 19 . However, lower than the study conducted in Jima Ethiopia, 41.1% 20 ; Eastern Ethiopia, 39.3% 21 ; Wolaita, Southern Ethiopia (49.8%) 22 and Kenya 36%) 23 .…”
Section: Discussioncontrasting
confidence: 57%